Hack proofing your e-commerce site the only way to stop a hacker is to think like one - Russell, Ryan.; Syngress Media, Inc. (Rockland, MA : Syngress, 2001)
From the authors of the bestselling Hack Proofing Your Network! Yahoo!, E-Bay, Amazon. Three of the most popular, well-established, and lavishly funded Web sites in existence, yet hackers managed to penetrate their security systems and cripple these and many other Web giants for almost 24 hours. E-Commerce giants, previously thought to be impenetrable are now being exposed as incredibly vulnerable. This book will give e-commerce architects and engineers insight into the tools and techniques used by hackers to compromise their sites. The security of e-commerce sites is even more imperative than non-commerce sites, because the site has the added responsibility of maintaining the security of their customer's personal and financial information. Hack Proofing Your E-Commerce Site will provide computer architects and engineers all of the information they need to design and implement security measures. * Heightened media awareness of malicious attacks against "secure" sites guarantees a wide audience * Uses forensics-based analysis to give the reader insight to the mind of a hacker. This understanding is crucial for security professionals to defend against attacks.
Authorship statement from cover.
Includes index.
Keywords: Electronic commerce -- Security measures; Business enterprises -- Computer networks -- Security measures; Internet -- Security measures; Electronic books